1994
DOI: 10.2307/1131393
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Health Knowledge in Low-Income Mexican-American Children

Abstract: Children growing up in poverty are at risk for various health problems. For low-income, Mexican-American children, these risks include obesity, diabetes, and accidental injuries, 3 conditions that can largely be prevented by healthy life-styles. Despite the potential for prevention through education leading to health-promoting behaviors, very little is known about the development of health knowledge in this population. The present study examined low-income, Mexican-American children's understanding of the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…In past studies (Burbach and Peterson 1986;Gilbert 1969;Olvera-Ezzell et al 1994 found to be the predictors of children's cognitive development regarding illness. But, this study reveals that ill family environment injects to sprout up more internal needs and external pressures of children than the healthy family environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In past studies (Burbach and Peterson 1986;Gilbert 1969;Olvera-Ezzell et al 1994 found to be the predictors of children's cognitive development regarding illness. But, this study reveals that ill family environment injects to sprout up more internal needs and external pressures of children than the healthy family environment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Burbach and Peterson 1986;Gilbert 1969;Olvera-Ezzell et al 1994;Robson 2000;Schvaneveldt et al 1990) suggest that growing age and low family income make the children aware of the causes and consequences of illness. Children having education are more aware about health and illness.…”
mentioning
confidence: 99%
“…Interview method was used in this study since it provided the best fit with the larger intervention study that it was part of. Although a substantial amount of information was obtained using the selected open-ended questions, the use of other complementary age-appropriate, child-friendly methods would facilitate more in-depth data in future studies (Mobley and Evashevski, 2000;Olvera-Ezzell et al, 1994). The definition of healthy provided to participants may have influenced some responses; however, the definition served as the basis for children to tell the researcher what they do to make themselves healthy and to ensure those who were unable to explain what health meant had the same basis to respond to the following questions.…”
Section: Limitationsmentioning
confidence: 99%
“…A number of studies have explored pre-school children's knowledge and understanding of specific health behaviours, for example, food and exercise (Anthamatten et al, 2013;Harrison et al, 2015;Macdonald et al, 2005;Matheson et al, 2002;Pearce et al, 2009;Protudjer et al, 2010;Schultz and Danford, 2016). Interestingly, research that has looked broadly at this population's understanding of health has found that children know the least about the relationship between food consumption, exercise and their health, and the most about beneficial and harmful practices in the areas of safety and hygiene (Mobley, 1996;Olvera-Ezzell et al, 1994). Pre-school children have also been found to view health as being able to participate in desired activities, being engaged and feeling good (Almqvist et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that included young children's perceptions regarding variables associated with healthy weight suggest that by age 3 most children have the cognitive ability to form rudimentary health concepts based on their life experiences (Mobley 1996). Nutrition knowledge lags behind health issues such as safety and hygiene (Olvera-Ezzell et al 1994), but is better developed than understanding of how physical activity benefits health (Lasky & Eichelberger 1985). While contextual realities may limit the application of health knowledge by pre-schoolers (Irwin et al 2006), health concepts appear to be domain-specific and more influenced by experience than cognitive development.…”
Section: Social Construction Of Young Children's Health Knowledgementioning
confidence: 99%